Perceived supervisor’s subclinical psychopathy, and subordinate’s organizational commitment, job satisfaction and satisfaction with executive - SANECKA, ELŻBIETA (Journal of Education Culture and Society, 2020)
This study was designed to investigate the correlations between supervisor`s perceived subclinical psychopathy and subordinate`s organizational commitment, overall job satisfac-tion and particularly satisfaction with his/her supervisor. The results, based on a sample of 153 employees, showed that subordinates working with leaders, who can be defined as orga-nizational (or industrial, corporate) psychopaths, tended to adopt more negative work attitu-des. Supervisor`s perceived subclinical psychopathy had a negative impact on subordinates’ job satisfaction, satisfaction with supervisor and their organizational commitment. The paper discusses the results and limitations of the study, and offers suggestions for future research.